Health benefits of seafood consumption - with special focus on household preparations and bioactivity in animal models - Jensen, Ida-Johanne (UiT The Arctic University of Norway, 2014)
The papers of this thesis are not available in Munin: 1. Jensen, I-J., Larsen, R., Rustad, T. and Eilertsen, K.E.: 'Nutritional content and bioactive properties of wild and farmed cod (Gadus morhua L.)', of Food Composition and Analysis (2013), vol.31:212-216. Available at http://dx.doi.org/10.1016/j.jfca.2013.05.013 2. Jensen, I-J. Dort, J. and Eilertsen, K.E.: 'Proximate composition, antihypertensive and antioxidative properties of the semimembranosus muscle from pork and beef after cooking and in vitro digestion', Meat Science (2014), vol. 96:916-921. Available at http://dx.doi.org/10.1016/j.meatsci.2013.10.014 3. Jensen, I-J., Eystuskard, J., Madetoja, M. and Eilertsen, K.E.: 'The potential of cod hydrolyzate to inhibit blood pressure in spontaneously hypertensive rats', Nutrition Research (2014), vol.34:168-173. Available at http://dx.doi.org/10.1016/j.nutres.2013.11.003 4. Jensen, I-J., Walquist, M., Liaset, B., Elvevoll, E.O. and Eilertsen, K.E.: 'Seafood protein reduce atherosclerotic burden in female apolipoprotein E deficient (apoE-/-) mice fed a Western type high fat diet for 13 weeks' (manuscript) Fish consumption is well acknowledged to reduce risk of cardiovascular disease, the health benefits mainly being associated with EPA and DHA. Increasing evidence, however, demonstrate that also the proteins and other bioactive compounds may be of relevance to human health. This project was initiated in order to examine the nutritional composition and bioactivity related to cardiovascular disease parameters in fish and terrestrial meat protein sources. The aims were limited to i) document differences in nutritional composition and in vitro bioactivity of wild and farmed Atlantic cod, pork and beef, ii) examine the impact of cooking and digestion on the nutrients and in vitro bioactive components and iii) evaluate the effects of different protein sources and bioactive peptides using animal models of hypertension and atherosclerosis. The nutritional contents of cod and terrestrial meats were comparable, the ...